Converting inert plastic waste into energetic materials: A study on the light-accelerated decomposition of plastic waste with the Fenton reaction. (May 2018) - Chow, Cheuk-Fai; Wong, Wing-Leung; Chan, Ching-Wan; Chan, Chung-Sum
Graphical abstract: Highlights: A new chemical approach to convert plastic to energetic material via a light-controlled reaction. Under ambient condition and within 1 h, plastic can be converted to thermal and mechanical energy. Heat (1800–3200 J/g) and CO2 (380–560 kPa/g) were generated through the activation of plastic. Abstract: Better treatment and management strategies than landfilling are needed to address the large quantities of unrecycled plastic waste generated by daily human activities. Waste-to-energy conversion is an ideal benchmark for developing future large-scale waste management technologies. The present study explores a new approach for producing energetic materials by converting inert plastic waste into energy (thermal and mechanical energies) via a light-controlled process through the simple chemical activation of plastic waste, including polyethylene, polypropylene, and polyvinyl chloride. The inert and non-polar polymer surfaces of the plastics were modified by generating a number of sulfonic groups (SO3 − ) using chlorosulfuric acid, followed by grafting of Fe(III) catalyst onto the polymer chains to obtain activated polymer. Elemental analyses of these activated materials showed that the carbon-to-sulfur ratio ranged from 3:1 to 5:1. The FTIR spectra indicated the presence of CC bonds ( v C=C : 1615–1630 cm −1 ) and SO bonds ( v S=O : 1151–1167 cm −1 ) in the activated polymers after chemical reaction. These activated materials were energetic, as light could be used to convert them into thermal (1800–3200 J/g) and mechanical energies (380–560 kPa/g) using hydrogen peroxide as the oxidant under ambient conditions within 1 h.